Definitive role of surgery in management of acromegaly due to ectopic growth hormone secretion: review of literature - Singh, Anuj; Sharma, Naveen; Shekhawat, Jaiveer S.; Singh, Mahaveer; Sherawat, Ram C.; Chaturvedi, Anushree (International Journal of Research in Medical Sciences, 2025)
Acromegaly, characterized by excessive growth hormone (GH) secretion, typically arises from pituitary adenomas. Ectopic GH production from non-pituitary tumors, such as carcinoid tumors, is exceedingly rare, <1%. The majority of the growth hormone-releasing hormone (GHRH) - secreting tumors are bronchial carcinoids. Other GHRH-secreting tumors in decreasing order of occurrence are pancreatic adenomas, gastro-intestinal tumors, thymic tumors, and tumors associated with the MEN-I syndrome. We present a case of a 43-year-old female who presented with features consistent with acromegaly and was found to have an ectopic source of GH from a mediastinal tumor. Diagnostic evaluation included biochemical testing, imaging studies, and histopathological confirmation. Surgical intervention led to complete resolution of clinical symptoms and normalization of GH levels. This case highlights the diagnostic challenges posed by ectopic GH secretion and emphasizes the critical role of surgery in achieving favorable outcomes in such rare presentations of acromegaly.